Tanggung Jawab Perwakilan Diplomatik Yang Melakukan Tindakan Penyalahgunaan Wewenang di Negara Penerima (Receiving State) - Tasya Rahim; Efie Baadila; Johanis Steny Franco Peilouw (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Diplomatic representatives who abuse this authority because of their inherent rights of immunity and immunity.Purposes of the Research: This study aims to identify and understand the responsibilities of diplomatic officials who commit acts of abuse of authority in the receiving country according to the 1961 Vienna Convention and to identify and understand the state's responsibility to diplomatic officials who commit acts of abuse of authority in the receiving country. Methods of the Research: This study uses normative legal research methods, using primary, secondary, tertiary legal sources and the collection of legal materials is carried out using library research. Furthermore, the analysis technique uses qualitative analysis and is presented descriptively, namely analyzing the legal material obtained based on the legal rules and to identify and conclude the results of the analysis in accordance with the problems raised.Results of the Research: The form of responsibility of a diplomatic representative or diplomatic official who abuses his authority in the country receiving the diplomatic official can receive consequences in Persona Non Grata, the immunities and privileges of diplomatic officials are removed and the sending country is recalled for trial. Forms of state accountability that can be carried out by North Korea (sending country) to Bangladesh (receiving country) include compensation and satisfaction. Compensation is a form of state responsibility in the form of money payments given due to material losses due to the actions of diplomatic officials who abuse their powers. While satisfaction is a form of state responsibility by apologizing for the actions of its diplomatic officials.